2015
DOI: 10.1186/s13287-015-0122-1
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo immunosuppressive effects of mesenchymal stem cells on Crohn’s disease mucosal T cells are largely dependent on indoleamine 2,3-dioxygenase activity and cell-cell contact

Abstract: IntroductionCrohn’s disease (CD) is a disabling chronic enteropathy sustained by a harmful T-cell response toward antigens of the gut microbiota in genetically susceptible subjects. Growing evidence highlights the safety and possible efficacy of mesenchymal stem cells (MSCs) as a new therapeutic tool for this condition. Therefore, we aimed to investigate the effects of bone marrow-derived MSCs on pathogenic T cells with a view to clinical application.MethodsT-cell lines from both inflamed and non-inflamed colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 68 publications
(77 reference statements)
1
29
0
Order By: Relevance
“…Adipose derived allo geneic stem cells have been considered as new treatment approaches for such fistulas 142,143 . Experimental studies revealed that mesenchymal stem cells (MSCs) might exert potent immunomodulatory effects on antigen specific T cells in Crohn's disease through paracrine and cell-cell contact mediated actions 144 . Clinically, local administration of allogeneic, expanded MSCs in initial trials was not associated with severe adverse events in patients with Crohn's disease who had perianal fistulas and seemed to promote healing.…”
Section: T Cellmentioning
confidence: 99%
“…Adipose derived allo geneic stem cells have been considered as new treatment approaches for such fistulas 142,143 . Experimental studies revealed that mesenchymal stem cells (MSCs) might exert potent immunomodulatory effects on antigen specific T cells in Crohn's disease through paracrine and cell-cell contact mediated actions 144 . Clinically, local administration of allogeneic, expanded MSCs in initial trials was not associated with severe adverse events in patients with Crohn's disease who had perianal fistulas and seemed to promote healing.…”
Section: T Cellmentioning
confidence: 99%
“…The downregulation of the immune system comes through the inhibition of dendritic cells from monocytes, the suppression of naïve and memory CD4+ cells, prevention of T cell activation by downregulating costimulatory molecules on mature dendritic cells and promotion of regulatory T cells 53–56. Interestingly, in vitro MSCs induce dendritic cells into a regulatory-like profile57 and shift the T cell population to a more tolerogenic pattern 58. Another unique property of MSCs that allows them to be valuable players in the tissue repair process is their ability to migrate to sites of tissue injury and inflammation 59.…”
Section: Future Strategies: Cell-based Therapy For Pfcdmentioning
confidence: 99%
“…In contrast, Luetzkendorf and colleagues extensively demonstrated an intact phenotype after MSC thawing under GMP conditions and a similar activity in the leukocyte proliferation assay[43,44]. Higher rate of MSC proliferation can be achieved with hypoxic conditions in culture, so as to reproduce the niche environment, whereas IFNγ/IFNγ + IL1-β pretreatment enhance IDO-mediated T-reg expansion[16,43,44]. …”
Section: Methods For Sorting Expansion and Storage: Application Of Gmpmentioning
confidence: 99%
“…The latter in turn catabolizes tryptophan producing kynurenins, a potent T-reg lymphocyte inducer[13,14]. MSC-dependent induction of IDO correlates with disease rating in humans[15,16] and, to a lesser extent, in mice where MSC anti-inflammatory action is mostly mediated by iNOS[13,17] (Table 1). Notably, IDO or iNOS-mediated MSC activity was recently shown to correlate with a specific phylogenetic tree (Figure 1)[13].…”
Section: Pharmacodynamic Aspects - Biological Effectsmentioning
confidence: 99%
See 1 more Smart Citation